2004
DOI: 10.1097/00004694-200411000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Distraction Osteogenesis in Short First Metatarsals

Abstract: The authors analyzed the results and complications of metatarsal lengthening in short first metatarsals by distraction osteogenesis. There were 13 first metatarsal lengthenings in eight patients. Mean age was 18.8 years and the average percentage of lengthening was 49.2%. The average healing index was 72.4 days/cm. The major complication was cavus foot, which was noticed in four feet. All great toes showed some loss of motion at metatarsophalangeal (MP) joint. Other complications were hallux valgus, angulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
12
1
Order By: Relevance
“…Our healing index for metatarsal lengthening is greater than the healing index reported by other authors [16,19]. We feel that these results are due to a greater amount of lengthening (average lengthening of 24.3 mm) achieved in our study compared with others (average lengthening not less than 17.6 mm) [4,12,17].…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Our healing index for metatarsal lengthening is greater than the healing index reported by other authors [16,19]. We feel that these results are due to a greater amount of lengthening (average lengthening of 24.3 mm) achieved in our study compared with others (average lengthening not less than 17.6 mm) [4,12,17].…”
Section: Discussioncontrasting
confidence: 58%
“…Many authors reported that a healing index of less than 1.5 months/cm could be achieved by applying an extension rhythm of 0.25 mm twice a day [4,12,17]. A healing index Fig.…”
Section: Discussionmentioning
confidence: 99%
“…stiffness or subluxation of the MTP joint, cavus or other angulation deformity of the metatarsus, prolonged time for bony consolidation, and pin tract infection (Table 2) (Kawashima et al 1994, Takakura et al 1997, Masada et al 1999, Oh et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…Surgery should be planned on the basis of functional recovery and anatomical restoration that restores proper weight bearing in addition to addressing cosmetic problems. Several techniques have been described for the treatment of brachymetatarsia; these include one-stage lengthening using an interpositional bone graft, gradual lengthening by distraction osteogenesis with or without shortening of the adjacent metatarsals and phalanges, and shortening of adjacent metatarsals and phalanges (Harris and Beath 1949, Hughes et al 1990, Kawashima et al 1994, Choi et al 1999, Masada et al 1999, Oh et al 2004). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation